Optimized Conditions for Electrical Tissue Stimulation with Biphasic, Charge-Balanced Impulses - Zhengwu Sun; Payel Sen; Jules Hamers; Thomas Seidel; Andreas Dendorfer; Petra Kameritsch (Bioengineering)
The cultivation of excitable cells typically profits from continuous electrical stimulation, but electrochemical consequences are mostly harmful and must be minimized. The properties of the electrode materials and stimulation impulses are key. Here, we developed an easy method to analyze the electrochemical impact of biphasic, current-controlled impulses, applied via graphite electrodes, using phenol red as the redox indicator. We also tested the stimulation conditions for the long-term cultivation of myocardial tissue. The colorimetric assay was able to detect ±0.2% deviations in typical positive and negative pulse charges. Phenol red was best preserved (20% degradation over 24 h) by impulses of equivalent positive and negative charges (full charge balance), generated with either manual calibration, capacitive electrode coupling, or feedback regulation of electrode polarization. Feedback regulation established full charge balance at pre-pulse voltages of about 300 mV, but also provided the option to selectively compensate irreversible electrode reactions. Modifications to shape and timing did not affect the electrochemical effects of symmetric impulses. Charge-balanced stimulation maintained more than 80% of the contractility of porcine left ventricular myocardium after 10 days of culture, whereas disbalances of 2–4% provoked weakening and discoloration of the tissues. Active polarization regulation, in contrast to capacitive electrode coupling, reproduced the biological advantages of full charge balance.